Design and synthesis of silicon-containing fatty acid amide derivatives as novel peroxisome proliferator-activated receptor (PPAR) agonists. Issue 16 (15th August 2015) - Kajita, Daisuke; Nakamura, Masaharu; Matsumoto, Yotaro; Ishikawa, Minoru; Hashimoto, Yuichi; Fujii, Shinya
Graphical abstract